First high-resolution analysis of the fundamental bands of 29SiD4 and 30SiD4: Line positions and strengths; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 225 - Sydow C. Christian; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Raspopova N. I. Natalya Ivanovna; Belova A. S. Anastasiya Sergeevna; Bauerekker Z. Zigurd; Ulenekov (Ulenikov) O. N. Oleg Nikolaevich (2019, 2019)
Title screen